Chinese monetary policy and the dollar peg - J. James Reade; Ulrich Volz (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2010)
This paper investigates to what extent Chinese monetary policy is constrained by the dollar peg. To this end, we use a cointegration framework to examine whether Chinese interest rates are driven by the Fed's policy. In a second step, we estimate a monetary model for China, in which we include also other monetary policy tools besides the central bank interest rate, namely reserve requirement ratios and open market operations. Our results suggest China has been relatively successful in isolating its monetary policy from the US policy and that the interest rate tool has not been effectively made use of. We therefore conclude that by employing capital controls and relying on other instruments than the interest rate China has been able to exert relatively autonomous monetary policy.
Keywords: C32; E52; F33; 330; Chinese monetary policy; monetary independence; cointegration; Geldpolitik; Zinspolitik; Fester Wechselkurs; US-Dollar; Kointegration; Schätzung; China; USA